Doing Transitions in the Life Course Processes and Practices - Stauber, Barbara; Walther, Andreas; Settersten, Jr (Life Course Research and Social Policies, 2022)
This open access book provides a unique research perspective on life course transitions. Here, transitions are understood as social processes and practices. Leveraging the recent "practice turn" in the social sciences, the contributors analyze how life course transitions are "done." This book introduces the concept of "doing transitions" and its implications for theories and methods. It presents fresh empirical research on "doing transitions" in different life phases (e.g., childhood, young adulthood, later life) and life domains (e.g., education, work, family, health, migration). It also emphasizes themes related to institutions and organizations, time and normativity, materialities (such as bodies, spaces, and artifacts), and the reproduction of social inequalities in education and welfare. In coupling this new perspective with empirical illustrations, this book is an indispensable resource for scholars from demography, sociology, psychology, social work and other scientific fields, as well as for students, counselors and practitioners, and policymakers.